Emergency department use: Is frequent use associated with a lack of primary care provider? - Palmer, Erin (College of Family Physicians of Canada, 2014)
OBJECTIVE: To determine if having a primary care provider is an important factor in frequency of emergency department (ED) use. DESIGN: Analysis of a central computerized health network database. SETTING: Three EDs in southern New Brunswick. PARTICIPANTS: All ED visits during 1 calendar year to an urban regional hospital (URH), an urban urgent care centre (UCC), and a rural community hospital (RCH) were captured. MAIN OUTCOME MEASURES: Patients with and without listed primary care providers were compared in terms of number of visits to the ED. A logistic regression analysis was used to determine factors predictive of frequent attendance. RESULTS: In total, 48 505, 41 004, and 27 900 visits were made to the URH, UCC, and RCH, respectively, in 2009. The proportion of patients with listed primary care providers was 36.6% for the URH, 37.1% for the UCC, and 89.4% for the RCH. Among ED patients at all sites, frequent attenders (4 or more visits to an ED in 1 year) were significantly more likely (59.6% vs 45.1%, P < .001) to have listed primary care providers. Other factors that predicted frequent use included attendance at a rural ED, female sex, and older age. CONCLUSION: This study characterizes attendance rates for 3 EDs in southern New Brunswick. Our findings highlight interesting differences between urban and rural ED populations, and suggest that frequent use of the ED might not be related to lack of a listed primary care provider.